PENGEMBANGAN MEDIA GRAFIS DALAM PEMBELAJARAN - Ahmad Manshur; Akhmad Rodhi (Pendidikan Agama Islam, 2020)
The use of media in the learning process is very important to support the learning process, in the modern era, graphic media is the most attractive medium, by using graphic media children can understand messages and help them to be more motivated to learn, the problem is when Graphic media is not able to develop and monotonous will make students tend to be bored and reduce motivation to learn, this paper, development of graphic media is something needs to develop, the affect children become active and have high learning motivation, several graphic media need to be developed such as Graphics, diagrams, charts, sketches, posters, comics, photo media, flannel boards and bulletin boards, educators (teachers) can present graphic media through visual media presenting, ideas through the presentation of words, sentences with numbers, and symbols or pictures. Graphics are used to attract attention, clarify the presentation of ideas, and illustrate facts, they are interesting and memorable. The advantages of graphic media can simplify and accelerate students' understanding of the message conveyed, increase student attention, and an affordable price. While the weakness of graphic media is requires special skills in its manufacture, especially for more complex graphics and the presentation of messages is only a visual element.